Analisa variasi temperatur terhadap nilai kekerasan aluminium pada proses squeeze casting - Tri Cahyo Wahyudi; Asroni Asroni (Universitas Muhammadiyah Metro, 2022)
Aluminum is a non-ferrous metal and has the advantages of light specific gravity, corrosion resistance. Aluminum can also be used in the manufacture of pistons, engine blocks, wheels, drums. Squezze casting is a casting process, where molten metal is poured and pressure is applied until the solidification process is complete. Using hydraulic pressure, this technique is able to improve the physical and mechanical properties, especially on aluminum base material. The research method uses the Squeeze Casting process with temperature variations of 300ºC, 400ºC, 500ºC, the pressure is 60 seconds,the pressure is 5 tons. Pressing time for 75 seconds and Vickers hardness test. The results of the highest hardness value are in specimens with a temperature of 500ºC, namely with a value of 60.2 HVN, and for the lowest hardness value are found in specimens with a temperature of 300ºC with a value of 48.9 HVN. As well as the results of the hardness test another is at a temperature of 400ºC to get a hardness value of 51.1 HVN. Based on the hardness test that has been carried out the most optimal hardness value is on a specimen with a temperature of 500ºC.